Construction and characterization of chimeric FcγR T cells for universal T cell therapy - Juanjuan Zhao; Manling Chen; Xudong Li; Zhaoqi Chen; Wei Li; Rongqun Guo; Min Wang; Zhongxing Jiang; Yongping Song; Jianxiang Wang; Delong Liu (Experimental Hematology & Oncology)
Abstract Background Several approaches are being explored for engineering off-the-shelf chimeric antigen receptor (CAR) T cells. In this study, we engineered chimeric Fcγ receptor (FcγR) T cells and tested their potential as a versatile platform for universal T cell therapy. Methods Chimeric FcγR (CFR) constructs were generated using three distinct forms of FcγR, namely CD16A, CD32A, and CD64. The functionality of CFR T cells was evaluated through degranulation assays, specific target lysis experiments, in vitro cytokine production analysis, and assessment of tumor xenograft destruction specificity in mouse models using different monoclonal antibodies (MoAbs). Results Three types of CFR T cells were engineered, 16s3, 32-8a, 64-8a CFR T cells. In the presence of rituximab (RTX), cytotoxicity of all three types of CFR T cells against CD20+ Raji-wt, K562-CD20+, and primary tumor cells was significantly higher than that of the mock T cells (P < 0.001). When herceptin was used, all three types of CFR T cells exhibited significant cytotoxicity against HER2+ cell lines of SK-BR-3, SK-OV-3, and HCC1954 (P < 0.001). The cytotoxicity of 64-8a CFR T cells was significantly inhibited by free human IgG at a physiological dose (P < 0.001), which was not observed in 16s3, 32-8a CFR T cells. Compared to 32-8a CFR T cells, 16s3 CFR T cells exhibited more prolonged cytotoxicity than 32-8a CFR T cells (P < 0.01). In in vivo assays using xenograft models, 16s3 CFR T cells significantly prolonged the survival of mice xenografted with Raji-wt cells in the presence of RTX (P < 0.001), and effectively reduced tumor burden in mice xenografted with SK-OV-3 cells in the presence of herceptin (P < 0.05). No significant non-specific cytotoxicity of CFR T cells was found in vivo. Conclusion The anti-tumor effects of the CFR T cells in vitro and in xenograft mouse models are mediated by specific MoAbs such as RTX and herceptin. The CFR T cells therefore have the features of universal T cells with specificity directed by MoAbs. 16s3 CFR T cells are chosen for clinical trials.